2020
DOI: 10.1038/s41545-020-0052-z
|View full text |Cite|
|
Sign up to set email alerts
|

Advancing electrodeionization with conductive ionomer binders that immobilize ion-exchange resin particles into porous wafer substrates

Abstract: Electrodeionization (EDI) is an electrically driven separations technology that employs ion-exchange membranes and resin particles. Deionization occurs under the influence of an applied electric field, facilitating continuous regeneration of the resins and supplementing ionic conductivity. While EDI is commercially used for ultrapure water production, material innovation is required for improving desalination performance and energy efficiency for treating alternative water supplies. This work reports a new cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…A recent study by Palakkal et al using SEM observed that polyethylene was partially covering their cation exchange resin (Purolite PFC100E) which had sulfonic acid functional groups and was a similar size to the Amberlite IR 120 Na + resins at around 0.3 to 0.5 mm [ 28 ]. When they used an ionomer binder rather than polyethylene, they observed significantly less coverage of their cation exchange resin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Palakkal et al using SEM observed that polyethylene was partially covering their cation exchange resin (Purolite PFC100E) which had sulfonic acid functional groups and was a similar size to the Amberlite IR 120 Na + resins at around 0.3 to 0.5 mm [ 28 ]. When they used an ionomer binder rather than polyethylene, they observed significantly less coverage of their cation exchange resin.…”
Section: Resultsmentioning
confidence: 99%
“…The wafer is a mixture of immobilized cation- and anion-exchange resins using a polymer as a binding agent. Compared to conventional EDI, WE-EDI can be easily built and run more efficiently, and it prevents uneven flow distribution and leakage of ions between the compartments simultaneously [ 28 ]. Because there is less leakage, WE-EDI can be used for more selective separations such as the removal of acidic impurities from corn stove hydrolysate liquor, CO 2 capture, and purification of organic acids [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ionomer binders strongly influence the performance and stability of numerous electrochemical processes such as fuel cells, [1][2][3][4] water 5 and carbon dioxide electrolyzers, 6 and deionization units. 7,8 In low-and high-temperature polymer electrolyte membrane (i.e., LT-PEM and HT-PEM) architectures involving hydrogen, the binders hold the electrocatalyst/electrocatalyst supports, while also delivering protons to and from the electrocatalyst to the PEM separator. Both PEM separators and ionomer electrode binders require high conductivity and stability 4,9 under a wide-range of conditions (e.g., chemical, electrochemical, and thermal), but there are nuanced differences with respect to the properties for PEM separators and electrode binders.…”
Section: Introductionmentioning
confidence: 99%
“…7 On top of these transport considerations, IEMs require mechanical integrity, 3,8 in the presence of liquids of varying composition (e.g., water-organic mixtures) and total dissolved salt (TDS) concentrations. These membranes oen physically separate two liquid compartments in electrodialysis 3 and electrodeionization 9,10 or electrodes when used in membrane capacitive deionization. 4 A subset of polymeric materials that has received signicant attention includes block copolymer electrolytes (BCEs) 11,12 as their percolated pathways of ionic domains ameliorate ionic conductivity and the non-ionic domains foster mechanical properties and curtail excess swelling.…”
Section: Introductionmentioning
confidence: 99%